Pengaruh Media Pembelajaran Interaktif dan Minat Belajar Terhadap Hasil Belajar IPA Siswa MI / SD - Didit Darmawan; Nadia Marta Trilova; Yeni Purwanti (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study aims to analyze the important role of forensic accounting and investigative auditing in the prevention and detection of fraud within organizations. The method used is a descriptive qualitative approach through a literature review by examining various sources related to the concepts, functions, and applications of forensic accounting and investigative auditing. The results of the study indicate that forensic accounting plays a strategic role in the preventive aspect, such as identifying weaknesses in internal control systems, analyzing fraud risks, and detecting early indications of fraud. Meanwhile, investigative auditing plays a role in the repressive aspect through in-depth examination processes, collection of legally valid evidence, analysis of fraud patterns, and identification of perpetrators and their modus operandi. The synergy between forensic accounting and investigative auditing is proven to enhance the effectiveness of fraud detection systems, produce more accurate investigation processes, and enable comprehensive fraud disclosure. Furthermore, the implementation of these approaches contributes to improving organizational accountability and transparency. Therefore, the integration of forensic accounting and investigative auditing becomes an essential element in establishing good governance and minimizing fraudulent practices.